2019
DOI: 10.3390/pharmacy7040138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Caregiving for Dementia Patients on Healthcare Utilization of Caregivers

Abstract: The elderly, whom are vulnerable to the physical, mental and chronic diseases of aging, are the fastest growing segment of the US population. Dementia is of particular concern in this population, and caregivers of people with dementia are subjected to psychological, physical, emotional and functional stress. The purpose of this study was to investigate the impact of caregiving for dementia patients on health care services utilization of caregivers and to examine if caregivers utilize more healthcare services t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Past studies have also shown that dementia caregivers tend to be at higher risk of hospitalization; this finding is true when compared to nondementia caregivers (Chan et al, 2018), to noncaregivers (Goren et al, 2016; Moore et al, 2001; Rahman et al, 2019), or to their own past history (Schubert et al, 2008; Toseland et al, 1999). In our study, the dementia caregivers tended to use more hospital resources than nondementia caregivers when their family member used a single LTC service, while nonsignificant relationship was found when the family member received multiple LTC services.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Past studies have also shown that dementia caregivers tend to be at higher risk of hospitalization; this finding is true when compared to nondementia caregivers (Chan et al, 2018), to noncaregivers (Goren et al, 2016; Moore et al, 2001; Rahman et al, 2019), or to their own past history (Schubert et al, 2008; Toseland et al, 1999). In our study, the dementia caregivers tended to use more hospital resources than nondementia caregivers when their family member used a single LTC service, while nonsignificant relationship was found when the family member received multiple LTC services.…”
Section: Discussionmentioning
confidence: 93%
“…Effective outpatient services might be able to prevent ED visits or hospitalizations (Lieu et al, 1997). Past studies have found that caregiving responsibilities can affect dementia caregivers’ healthcare utilization and costs (Bremer et al, 2015; Chan et al, 2018; Goren et al, 2016; Moore et al, 2001; Pruchno & Potashnik, 1989; Rahman et al, 2019; Schubert et al, 2008; Toseland et al, 1999; Van Houtven et al, 2005; Zhu et al, 2015). Dementia caregivers have been reported to use outpatient services and hospitalizations most frequently (Toseland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with existing evidence for other caregiving populations ( e . g ., those caring for dementia patients) that also found greater health care utilization among the caregivers [ 21 , 22 ]. This study was conducted in a longitudinal setting among mothers in Denmark, where the national health care system fully covers primary, specialist, inpatient, and mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Up to one third of family caregivers report anxiety and/or depression, suggesting a significant mental health toll related to the caregiving experience (Schulz and Martire 2004;Sheehan et al 2021). In addition, caregivers are at risk for developing stressrelated health problems such as hypertension, heart disease, and compromised immunity (Rahman et al 2019;Vitaliano et al 2005). A sense of perceived burden may emerge due to the ongoing stressors associated with caregiving (Armstrong et al 2019;Schulz and Eden 2016;Thompson et al 2005).…”
Section: Impacts On Family Caregivers Of Persons Living With Dementiamentioning
confidence: 99%